A Privacy Preserving Method in WSN - Ping Qian; Meng Wu (Dianxin kexue)
A great challenge to wireless sensor network（WSN）is how to protect privacy from disclosing during application in WSN as well as obtain accurate results. In recent years, researchers at home and abroad have done much work on privacy preserving in WSN. This paper surveyed the general privacy preserving methods from two aspects of location privacy and data privacy in WSN and analyzed their theories and characteristics. A new method based on multi-notes phantom routing protocols and ECC homomorphic encryption was proposed, which could protect location privacy and data privacy at the same time. Compared to current methods, better privacy will be protected and less energy will be consumed.